Glass fiber sizing agent and preparation method and application thereof
By developing a glass fiber wetting agent containing components such as silane coupling agent, the problems of low mechanical strength and general high temperature resistance in the field of high-strength special yarns are solved, and glass fiber yarns with high strength, high interface bonding and high temperature stability are achieved, which are suitable for high-strength applications in composite materials.
Patent Information
- Application Number
- CN202311761891.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-12-20
- Publication Date
- 2025-04-29
- Estimated Expiration
- 2043-12-20
AI Technical Summary
Traditional glass fiber materials have problems such as low mechanical strength, high temperature resistance and general damage resistance in the field of high-strength special yarns, which limits their reliability and durability.
A glass fiber wetting agent is developed, including silane coupling agent, film forming agent, lubricant, wetting agent, surfactant, dry strength agent, leveling agent and pH adjuster, with a solid content of 6.0% to 8.0%, to improve the high strength, high interfacial bonding and high temperature stability of glass fiber yarns.
By using the glass fiber yarn produced by the wetting agent, high strength, high interfacial bonding and high temperature stability are achieved, excellent chemical compatibility and permeability, and are suitable for the preparation of composite materials in the high-strength field.
Smart Images

Figure BDA0004618805000000021 
Figure BDA0004618805000000022 
Figure BDA0004618805000000111
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of glass fiber reinforced thermosetting resins, and in particular to a glass fiber sizing agent and a preparation method and application thereof. Background Art
[0002] In the 1960s, the United States successfully applied glass fiber reinforced composite materials to engine casings. In addition, the US "Red Eye" infrared ground-to-air launch tube, which weighs only 10.5kg, also uses glass fiber reinforced epoxy resin-based composite materials. At present, almost all helicopter main blades in my country use my country's independently developed high-strength No. 4 glass fiber as a composite reinforcement base material to replace metal blades, and the service life is several times that of metal blades. In the field of high-strength special yarns, high-strength special glass fibers have been widely used in helicopter rotors, "Glare" plates for aircraft, engine casings, rocket launch tubes, high-pressure storage containers and other fields.
[0003] However, traditional glass fiber materials have problems such as low mechanical strength, high temperature resistance and general damage resistance, which limit their reliability and durability in the field of high-strength special yarns. For example, the launch tube requires high strength performance, so that the maximum charge of the launch tube can be increased, the maximum gas flow pressure in the tube can be increased, and a higher initial velocity of the projectile can be generated, thereby increasing the power of the launch tube. In addition, high strength and high temperature stability also ensure safety during launch. In order to solve the above problems, it is necessary to develop a glass fiber impregnation agent, which has the characteristics of high strength, high interface bonding and high temperature stability. This product has very high requirements on the mechanical properties and process properties of glass fiber. First of all, the glass fiber yarn itself must have high strength and high temperature stability. When used as a composite material substrate, it further improves the mechanical properties of the glass fiber composite material and ensures safety and practicality during use. In addition, the mechanical stress transfer between the glass fiber and the resin matrix must be high, which requires excellent chemical compatibility, better interface bonding strength and excellent permeability between the glass fiber and the resin, which can prevent the occurrence of peeling and have high-strength mechanical properties. Finally, the glass fiber yarn is required to be smooth to use, with less hairiness, good processability and designability, and suitable for winding, pultrusion and prepreg processes. Therefore, it is necessary to develop a sizing agent suitable for glass fiber yarns used in high-strength fields, which can better wrap and wrap evenly in the glass fiber structure, have high strength and high temperature resistance, and have better interface bonding with the resin, further improving the mechanical properties of the composite material. Summary of the invention
[0004] The present application aims to provide a glass fiber impregnating agent. The glass fiber yarn produced by using the impregnating agent has the characteristics of high strength, high interface bonding and high temperature stability, and has excellent compatibility and interface bonding strength with epoxy resin; and the glass fiber yarn is smooth to use, has less product hairiness, and has good processability and designability.
[0005] According to the first aspect of the present application, a glass fiber sizing is provided, comprising effective components and water, wherein the solid content of the sizing is 6.0% to 8.0%, and the effective components include a silane coupling agent, a film-forming agent, a lubricant, a wetting agent, a surfactant, a dry strength agent, a leveling agent, and a pH regulator. The percentage of the solid mass of each effective component of the sizing to the total solid weight of the sizing is expressed as follows:
[0006]
[0007] Wherein, the silane coupling agent is a mixture of an aminosilane coupling agent and an epoxysilane coupling agent;
[0008] The film-forming agent is a mixture of bisphenol F epoxy emulsion, polyurethane emulsion and polyimide emulsion.
[0009] Preferably, the glass fiber sizing agent comprises effective components and water, the solid content of the sizing agent is 6.0% to 8.0%, the effective components include silane coupling agent, film former, lubricant, wetting agent, surfactant, dry strength agent, leveling agent and pH adjuster, and the percentage of the solid mass of each effective component of the sizing agent to the total solid weight of the sizing agent is expressed as follows:
[0010]
[0011] Wherein, the silane coupling agent is a mixture of an aminosilane coupling agent and an epoxysilane coupling agent;
[0012] The film-forming agent is a mixture of bisphenol F epoxy emulsion, polyurethane emulsion and polyimide emulsion.
[0013] Preferably, the aminosilane coupling agent is a bisaminosilane coupling agent, and the bisaminosilane coupling agent is selected from one or more of N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, and N-2-aminoethyl-3-aminopropyltriethoxysilane.
[0014] Preferably, the epoxy silane coupling agent is an aliphatic epoxy silane coupling agent, and the aliphatic epoxy silane coupling agent is selected from one or both of 3-glycidyloxypropyltrimethoxysilane and γ-glycidoxypropyltrimethoxysilane.
[0015] Preferably, the mass ratio C1 of the aminosilane coupling agent to the epoxysilane coupling agent is 4:1 to 2:1.
[0016] Preferably, the bisphenol F epoxy emulsion is a nonionic bisphenol F epoxy emulsion, the polyurethane emulsion is a cross-linked modified polyurethane emulsion, and the polyimide emulsion is a thermosetting polyimide emulsion.
[0017] Preferably, the nonionic bisphenol F epoxy emulsion has a molecular weight of 300-500, a viscosity of 2000-5000 mPa·s, and an epoxy equivalent of 170-200 g / mol.
[0018] Preferably, the molecular weight of the cross-linked modified polyurethane emulsion is 5000-10000, and the particle size is 0.1 μm-2 μm.
[0019] Preferably, the molecular weight of the thermosetting polyimide emulsion is 1500-2500, and the glass transition temperature is above 300°C.
[0020] Preferably, a solid mass ratio C2 of the bisphenol F epoxy emulsion, the polyurethane emulsion and the polyimide emulsion is 3:1:0.5 to 4:1:1.
[0021] Preferably, the lubricant is a silicone-modified lubricant.
[0022] Preferably, the wetting agent is a polyether-modified silicon wetting agent.
[0023] Preferably, the surfactant is selected from one or both of alkoxylated amine surfactants and alkoxy imidazoline surfactants.
[0024] Preferably, the dry strength agent is one or both of polyacrylamide and polyvinyl alcohol.
[0025] Preferably, the leveling agent is an organic siloxane compound.
[0026] Preferably, the pH adjuster is citric acid and / or glacial acetic acid.
[0027] According to a second aspect of the present application, a method for preparing the aforementioned glass fiber sizing is provided, comprising the following steps:
[0028] In water accounting for 35% to 50% of the total mass of the impregnant, a pH regulator and a silane coupling agent are sequentially added, and stirred evenly to obtain a solution containing a silane coupling agent;
[0029] Dilute the surfactant with 50°C hot water and stir evenly to obtain a surfactant solution;
[0030] The film former, lubricant, wetting agent, leveling agent, dry strength agent and solution containing silane coupling agent diluted with water are stirred evenly, then the surfactant solution is added and stirred evenly, and the remaining amount of water is supplemented and stirred evenly to obtain the glass fiber sizing agent.
[0031] According to a third aspect of the present application, a glass fiber produced by coating the aforementioned glass fiber sizing agent is provided.
[0032] According to a fourth aspect of the present application, there is provided a use of the aforementioned glass fiber sizing agent in the field of high-strength glass fiber composite materials.
[0033] The glass fiber yarn produced by using the glass impregnating agent of the present application has the characteristics of high strength, high interface bonding and high temperature stability, excellent chemical compatibility, higher interface bonding strength and excellent permeability; moreover, the yarn is smooth to use and the product has less hairiness. DETAILED DESCRIPTION
[0034] In order to make the purpose, technical scheme and advantages of the embodiments of the present application clearer, the technical scheme of the present application will be clearly and completely described below in conjunction with the embodiments of the present application. Obviously, the described embodiments are part of the embodiments of the present application, rather than all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without making creative work are within the scope of protection of the present application. It should be noted that, in the absence of conflict, the embodiments in the present application and the features in the embodiments can be arbitrarily combined with each other.
[0035] In some optional embodiments, a glass fiber sizing agent is provided, comprising effective components and water, wherein the solid content of the sizing agent is 6.0% to 8.0%, and the effective components include silane coupling agent, film-forming agent, lubricant, wetting agent, surfactant, dry strength agent, leveling agent and pH regulator, and the percentage of the solid mass of each effective component of the sizing agent to the total solid weight of the sizing agent is expressed as follows: silane coupling agent 10% to 28%; film-forming agent 40% to 75%; lubricant 4% to 14%; wetting agent 2% to 6%; surfactant 2% to 7%; dry strength agent 2% to 10%; leveling agent 1% to 6%; pH regulator 1% to 7%; wherein the silane coupling agent is a mixture of an aminosilane coupling agent and an epoxysilane coupling agent; and the film-forming agent is a mixture of a bisphenol F epoxy emulsion, a polyurethane emulsion and a polyimide emulsion.
[0036] In some optional embodiments, the glass fiber wetting agent includes effective components and water, the solid content of the wetting agent is 6.0% to 8.0%, the effective components include silane coupling agent, film-forming agent, lubricant, wetting agent, surfactant, dry strength agent, leveling agent and pH adjuster, and the percentage of the solid mass of each effective component of the wetting agent to the total solid weight of the wetting agent is expressed as follows: silane coupling agent 14% to 24%; film-forming agent 46% to 68%; lubricant 6% to 12%; wetting agent 3% to 6%; surfactant 3% to 6%; dry strength agent 4% to 10%; leveling agent 2% to 6%; pH adjuster 2% to 5%; wherein the silane coupling agent is a mixture of aminosilane coupling agent and epoxysilane coupling agent; the film-forming agent is a mixture of bisphenol F epoxy emulsion, polyurethane emulsion and polyimide emulsion.
[0037] In some optional embodiments, the glass fiber wetting agent includes effective components and water, the solid content of the wetting agent is 6.0% to 8.0%, the effective components include silane coupling agent, film-forming agent, lubricant, wetting agent, surfactant, dry strength agent, leveling agent and pH adjuster, and the percentage of the solid mass of each effective component of the wetting agent to the total solid weight of the wetting agent is expressed as follows: silane coupling agent 16% to 20%; film-forming agent 52% to 60%; lubricant 6% to 8%; wetting agent 4% to 6%; surfactant 3% to 5%; dry strength agent 5% to 7%; leveling agent 2% to 4%; pH adjuster 2% to 4%; wherein the silane coupling agent is a mixture of aminosilane coupling agent and epoxysilane coupling agent; the film-forming agent is a mixture of bisphenol F epoxy emulsion, polyurethane emulsion and polyimide emulsion.
[0038] In the present application, silane coupling agent can change the interfacial energy between inorganic matter and high molecular polymer, and form chemical or physical "molecular bridge" between interfaces, so that inorganic glass fiber and organic high molecular polymer are firmly combined. Silane coupling agent not only effectively transfers the high molecular polymer with low stress intensity and modulus acting on composite material to the glass fiber with high strength and modulus, makes full use of the high strength and high modulus characteristics of glass fiber, and can greatly improve many application properties of composite material, such as mechanical properties, electrical properties, and aging resistance. The silane coupling agent of the present application is a mixture of aminosilane coupling agent and epoxysilane coupling agent. Aminosilane coupling agent can be said to be universal, and can react with resins such as epoxy, phenolic, melamine, polyurethane to form covalent bonds, thereby improving the bonding force between resin and glass fiber, and aminosilane group can build bridges between glass fiber and resin in addition, improve the wetting property and spreading property of resin on the surface, and can improve the chemical resistance of resin substrate. Epoxy silane coupling agents can be firmly combined in different materials (such as unsaturated polyester); in addition, epoxy coupling agents have good compatibility with epoxy resins, can form covalent bonds with epoxy resins, and achieve strong bonding properties; and epoxy coupling agents have good water resistance and weather resistance. The amount of silane coupling agent used in this application is very important. If the amount of silane coupling agent used is too little, the coverage of the coupling agent on the interface will not be high enough, resulting in a weakening of the interfacial bonding strength; and if the amount of silane coupling agent used is too high, it will cause too many cross-linked structures, resulting in increased rigidity of the material, decreased toughness, and making the material brittle. In this application, the solid mass of the silane coupling agent accounts for 10% to 28% of the total solid mass of the impregnant, preferably 14% to 24%, further preferably 16% to 20%, and most preferably 16% to 18%.
[0039] The film former is the main component of the sizing agent. The performance of the film former directly determines the application effect of the sizing agent, and has an important impact on the performance and quality of the raw silk and yarn. The film former of the present application is a mixture of bisphenol F epoxy emulsion, polyurethane emulsion and polyimide emulsion. The bisphenol F epoxy emulsion compound contains polar groups such as aliphatic hydroxyl and ether groups, which make the bisphenol F epoxy emulsion molecules and the adjacent surfaces produce electromagnetic or chemical attraction, so the bisphenol F epoxy emulsion has excellent adhesion and clustering properties for glass fibers. Secondly, since the epoxy group can form a chemical bond with the unsaturated bond in the enhanced matrix resin, the bisphenol F epoxy emulsion has excellent permeability and wettability, especially when the matrix resin is an epoxy resin, the bisphenol F epoxy emulsion has excellent compatibility and interface; in addition, since the mechanical properties and corrosion resistance of the bisphenol F epoxy emulsion are excellent, and the viscosity is small, it has good impregnation properties for glass fibers. Polyurethane emulsion has inherent advantages such as high strength, wear resistance, and high elasticity, and a small amount of polyurethane emulsion can make the film flexible and have good bonding properties. Polyimide emulsion has good high temperature stability, mechanical properties, chemical stability, acid and alkali resistance, and dimensional stability, which makes it play a role in high-precision and high-temperature stable applications. This application requires reasonable control of the amount of film-forming agent so that the precursor has excellent bundling, bonding ability, flexibility and high-temperature stability, avoids glass fiber and precursor from breaking and mechanical wear, and meets the requirements of glass fiber post-processing, composite material processing technology and application performance. In this application, the solid mass of the film-forming agent after dehydration accounts for 40% to 75% of the total solid mass of the impregnating agent, preferably 46% to 68%, further preferably 52% to 60%, and most preferably 55% to 58%.
[0040] The lubricant can effectively lubricate and protect the monofilaments by the sizing agent. The use of the lubricant mainly satisfies the lubrication effect of the glass fiber during drawing, post-processing, and use. However, too much lubricant will affect the bundling of the glass fiber and the mechanical properties of the final FRP product. In the present application, the solid mass of the lubricant is controlled to account for 4% to 14% of the total solid content of the sizing agent, preferably 6% to 12%, and more preferably 6% to 8%.
[0041] The wetting agent can reduce the overall surface tension of the sizing agent, making it easier for the sizing agent to wet the surface of the glass fiber and achieve the effect of uniformly impregnating the raw silk. The wetting agent can also improve the resin's wetting of the surface of the glass fiber coated with the sizing agent and the penetration into the raw silk, that is, between the single silks, accelerate the penetration speed of the glass fiber in the matrix resin, enhance the interface bonding between the glass fiber and the matrix resin, and improve the mechanical strength of the composite material. The wetting agent can accelerate the speed at which the liquid enters the solid, thereby shortening the wetting time, which is beneficial to improving production efficiency. The present application needs to reasonably control the amount of the wetting agent. Too little wetting agent will lead to uneven wetting and penetration, and too much wetting agent will affect other properties of the sizing agent. In the present application, the solid mass of the wetting agent after dehydration accounts for 2% to 6% of the total solid mass of the sizing agent, preferably 3% to 6%, further preferably 4% to 6%, and most preferably 4% to 5%.
[0042] In the present application, the surfactant is used to eliminate static electricity in the impregnation agent and to improve the penetration effect. Glass fiber and its products often generate static electricity due to friction, which affects the application performance of the products. If the fiber has static electricity, it often has disadvantages such as "sticking" or "static stickiness", easy to absorb dust or get dirty. In the present application, it is necessary to reasonably control the amount of surfactant. Too little surfactant cannot eliminate static electricity, and too much surfactant will cause charge enrichment, resulting in poor penetration effect. In the present application, the solid mass of the surfactant after dehydration accounts for 2% to 7% of the total solid mass of the impregnation agent, preferably 3% to 6%, more preferably 3% to 5%, and most preferably 3% to 4%.
[0043] The dry strength agent can further improve the strength of the glass fiber yarn. In addition to the glass fiber itself, the strength of the glass fiber yarn is closely related to the wetting agent. The wetting agent can make the organic polymer and the surface of the glass fiber produce bonding behaviors such as chemical bonds or physical adsorption, thereby improving the mechanical properties. Most dry strength agents are high molecular polymers containing polyhydroxy groups or high molecular polymers containing amide groups, which are easy to form hydrogen bonds. After combining with the glass fiber, they prevent the expansion of glass fiber cracks and enhance the internal bonding force of the glass fiber, thereby improving the strength of the glass fiber yarn. In this application, the solid mass of the dry strength agent after dehydration accounts for 2% to 10% of the total solid weight of the wetting agent, preferably 4% to 10%, more preferably 5% to 7%, and most preferably 5% to 6%.
[0044] The leveling agent can improve the leveling performance of the sizing agent and prevent the glass fiber from having problems such as shrinkage cavities and unevenness. The leveling agent can also make the surface tension of the sizing agent uniform, play a role in wetting and leveling, and form a smooth, flat, and uniform coating film, which is conducive to the rapid penetration of the resin to achieve complete penetration. At the same time, the leveling agent also has an anti-scratch function. In this application, the solid mass of the leveling agent after dehydration accounts for 1% to 6% of the total solid weight of the sizing agent, preferably 2% to 6%, more preferably 2% to 4%, and most preferably 3% to 4%.
[0045] The pH value regulator of the present application is mainly used to promote the hydrolysis of the silane coupling agent and adjust the pH value of the impregnant, so that the pH value of the impregnant is controlled at 5 to 6. In the present application, the solid mass of the pH value regulator after dehydration accounts for 1% to 7% of the total solid weight of the impregnant, preferably 2% to 5%, more preferably 2% to 4%, and most preferably 2% to 3%.
[0046] In some optional embodiments, the aminosilane coupling agent is a bisaminosilane coupling agent. There are two amino functional groups in the molecular structure of the bisaminosilane coupling agent, a primary amine and a secondary amine, and this reactivity can enhance the bonding and adhesion with the surface of the glass fiber. In addition, the molecular polarity of the bisaminosilane coupling agent is large, the surface tension is low, and it is more conducive to the expansion on the surface of the glass fiber cloth. In some optional embodiments, the bisaminosilane coupling agent can be N-2-(aminoethyl)-3-aminopropyltrimethoxysilane (such as: Maitu A-1120), N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane (such as: Maitu A-2120), N-2-aminoethyl-3-aminopropyltriethoxysilane (such as Z-6021).
[0047] In some optional embodiments, the epoxy coupling agent is an aliphatic epoxy coupling agent. The aliphatic epoxy coupling agent has a long-chain aliphatic structure, which gives it a certain flexibility and makes the yarn more plastic. In some optional embodiments, the aliphatic epoxy silane coupling agent can be 3-glycidyloxypropyltrimethoxysilane (such as Maitu A-187) or γ-glycidoxypropyltrimethoxysilane (such as Z-6040).
[0048] In some optional embodiments, the mass ratio C1 of the aminosilane coupling agent to the epoxysilane coupling agent is 4:1 to 2:1.
[0049] The mass ratio of aminosilane coupling agent to epoxysilane coupling agent is very important in this application. If the amount of amino coupling agent is too high, it is easy to cause unstable reaction, while the amount of amino coupling agent is too low to form self-polymerization products or too many layers of polymers on the surface; in addition, taking epoxy resin as an example, the use of amino coupling agent can optimize the dispersion of glass fiber in epoxy resin and reduce the agglomeration of fillers, and epoxy coupling agent as an auxiliary agent can further improve the interface between glass fiber and epoxy resin, making the interface bonding stronger and more stable, allowing it to have better penetration and more complete, as well as excellent mechanical properties. When the mass ratio C1 of aminosilane coupling agent to epoxysilane coupling agent is 2:1 to 4:1, the sizing agent prepared by combining aminosilane coupling agent, epoxysilane coupling agent, and other components has good performance, and the glass fiber produced by the sizing agent also has good performance. For example, the mass ratio C1 of the aminosilane coupling agent to the epoxysilane coupling agent is 2:1, 2.4:1, 2.5:1, 3.5:1, 4:1.
[0050] In some optional embodiments, the bisphenol F type epoxy emulsion is selected from nonionic bisphenol F epoxy emulsion. Nonionic bisphenol F epoxy emulsion has low viscosity, is easier to flow during use, is convenient for coating, and has good wetting and impregnation effect on glass fiber. At the same time, since nonionic bisphenol F epoxy emulsion is uncharged, the use process is more stable. In some optional embodiments, the molecular weight of nonionic bisphenol F epoxy emulsion can be 300-500, the viscosity can be 2000-5000mPa·s, and the epoxy equivalent can be 170-200g / mol.
[0051] In some optional embodiments, the polyurethane emulsion is a cross-linked modified polyurethane emulsion. Since the cross-linked modified polyurethane emulsion has a cross-linked structure, it will show better wear resistance and heat resistance after curing. In some optional embodiments, the molecular weight of the cross-linked modified polyurethane emulsion can be 5000-10000, and the particle size can be 0.1μm-2μm.
[0052] In some optional embodiments, the polyimide emulsion is a thermosetting polyimide emulsion. Since the subsequent use process requires high temperature resistance, the thermosetting polyimide emulsion not only has excellent mechanical properties, but also has excellent high temperature resistance, which can meet the requirements of the subsequent process. In some optional embodiments, the molecular weight of the thermosetting polyimide emulsion can be 1500-2500, and the glass transition temperature can be above 300°C.
[0053] In some optional embodiments, a solid mass ratio C2 of the bisphenol F epoxy emulsion, the polyurethane emulsion and the polyimide emulsion is 3:1:0.5 to 4:1:1.
[0054] In the present application, the mass ratio of bisphenol F epoxy emulsion, polyurethane emulsion and polyimide emulsion will affect the performance of the prepared glass fiber. If the amount of polyimide emulsion is too much, the sizing agent will become brittle after film formation, thereby reducing the performance of the glass fiber. In the present application, when the solid mass ratio C2 of bisphenol F epoxy emulsion, polyurethane emulsion and polyimide emulsion is 3:1:0.5 to 4:1:1, the prepared glass fiber has excellent properties. Exemplarily, the solid mass ratio C2 of bisphenol F epoxy emulsion, polyurethane emulsion and polyimide emulsion is 3:1:0.5, 3.5:1:0.5, 4:1:0.5, 3:1:1, 3.5:1:1, 4:1:1.
[0055] In some optional embodiments, the lubricant is a silicone modified lubricant. The silicone modified lubricant has excellent high temperature resistance, chemical stability and low volatility, and plays an important role in lubrication, anti-adhesion, friction reduction and material protection. Since the structure of the silicone modified lubricant is similar to that of the silane coupling agent, it can effectively fill the micro cracks on the surface of the glass fiber, thereby reducing the generation of hairiness, improving the surface scratch resistance, reducing the surface friction coefficient, and improving the processing performance.
[0056] In some optional embodiments, the wetting agent is a polyether-modified silicon-based wetting agent. The polyether-modified silicon-based wetting agent has a relatively small molecular weight, and a large number of CH3 chains extend outward, which greatly reduces the surface tension and can further improve the wetting performance of the wetting agent. In addition, the polyether-modified silicon-based wetting agent has better stability at different pH and temperature.
[0057] In some optional embodiments, the surfactant is selected from one or both of alkoxylated amine surfactants and alkoxy imidazoline surfactants. Both alkoxylated amine surfactants and alkoxy imidazoline surfactants are cationic surfactants, which adsorb on the fiber surface with positively charged ions to form a directional adsorption film composed of hydrocarbon chains on the fiber surface. This adsorption film can not only effectively reduce the frictional charging phenomenon on the fiber surface, but also increase the humidity on the glass fiber surface and improve the penetration effect of the sizing agent.
[0058] In some optional embodiments, the dry strength agent is selected from one or both of polyacrylamide and polyvinyl alcohol. Since the polyacrylamide structural unit contains amide groups, it is easy to form hydrogen bonds, so that it has good water solubility and high chemical activity, and can enhance the ability to effectively combine with the silanol groups in the glass fiber, thereby improving the strength of the glass fiber yarn. Polyvinyl alcohol contains a large number of hydroxyl groups, which are easy to form hydrogen bonds with water molecules and can still form a strong bond after the yarn ball is dried.
[0059] In some optional embodiments, the leveling agent is an organic siloxane compound. The organic group of the organic siloxane compound helps to improve the compatibility of siloxane and the resin matrix, can provide uniform surface tension, enhance wettability to the resin substrate, and improve adhesion.
[0060] In some optional embodiments, the pH adjuster is citric acid and / or glacial acetic acid.
[0061] In some optional embodiments, a method for preparing the aforementioned glass fiber sizing is provided, comprising the following steps:
[0062] In water accounting for 35% to 50% of the total mass of the impregnant, a pH regulator and a silane coupling agent are sequentially added, and stirred evenly to obtain a solution containing a silane coupling agent;
[0063] Dilute the surfactant with 50°C hot water and stir evenly to obtain a surfactant solution;
[0064] The film former, lubricant, wetting agent, leveling agent, dry strength agent and solution containing silane coupling agent diluted with water are stirred evenly, then the surfactant solution is added and stirred evenly, and the remaining amount of water is supplemented and stirred evenly to obtain the glass fiber sizing agent.
[0065] In some optional embodiments, the method for preparing the glass fiber sizing comprises the following steps:
[0066] (1) adding 35% to 50% of the total mass of the wetting agent into a container, and sequentially adding a pH adjuster and a silane coupling agent, stirring evenly to obtain a solution containing a silane coupling agent;
[0067] (2) diluting the film-forming agent with a small amount of water and adding the diluted film-forming agent into the container, wherein the mass of the water is 3-5 times the mass of the film-forming agent;
[0068] (3) diluting the lubricant with water and adding it into the container, wherein the mass of the water is 5 to 6 times the mass of the lubricant;
[0069] (4) diluting the wetting agent with water and adding it into the container, wherein the mass of the water is 5 to 8 times the mass of the wetting agent;
[0070] (5) diluting the dry strength agent with water and adding it into the container, wherein the mass of the water is 6 to 8 times the mass of the dry strength agent;
[0071] (6) diluting the leveling agent with water and adding it into the container, wherein the mass of the water is 6 to 8 times the mass of the leveling agent;
[0072] (7) diluting the surfactant with warm water at about 50° C. and adding the diluted surfactant to the container, wherein the mass of the water is 5 to 6 times the mass of the surfactant;
[0073] (8) Add the remaining amount of water to the container and stir evenly to obtain a glass fiber sizing agent.
[0074] In some optional embodiments, a glass fiber produced by coating the glass fiber sizing agent is provided.
[0075] In some optional embodiments, there is provided an application of the aforementioned glass fiber sizing agent in the field of high-strength glass fiber composite materials.
[0076] The glass fiber yarn produced using the impregnating agent of the present application has the characteristics of high strength, high interface bonding and high temperature stability, excellent chemical compatibility, higher interface bonding strength and excellent permeability; the glass fiber yarn is smooth to use, has less product hairiness, has good processability and designability, and is particularly suitable for winding processes. It is also suitable for pultrusion and prepreg processes, and is suitable for the preparation of high-pressure storage containers, launch tubes, engine casings and other fields.
[0077] In order to further illustrate the beneficial effects of the types of components and the range of component contents selected in the glass fiber sizing of the present application, some examples of values of the components included in the glass fiber sizing of the present application are listed below.
[0078] The specific formulas of Examples 1 to 10 of the glass fiber sizing of the present application are shown in Table 1. The values in Table 1 are the percentages of the solid weight of each component of the effective component to the total solid weight of the sizing.
[0079] Table 1 The proportion of each group of the wetting agent in the embodiment
[0080]
[0081]
[0082] Table 1 (Continued) Distribution ratio of each group of wetting agent in the embodiment
[0083]
[0084]
[0085] In order to better illustrate the present application, the following examples are further listed. The following examples limit the specific product brand of each component. It should be noted that the following description is used to explain the present application, rather than to limit the scope of the present application in any way.
[0086] Example A1
[0087] The solid content of the impregnant is 6.0%, and the weight of each component of the effective component as a percentage of the total weight of the impregnant solid is expressed as follows:
[0088]
[0089] Example A2
[0090] The solid content of the wetting agent is 7.0%, and the weight of each component of the effective component as a percentage of the total weight of the solid of the wetting agent is expressed as follows:
[0091]
[0092]
[0093] Comparative Example 1
[0094] The solid content of the wetting agent is 6.0%. The percentage of the mass of each component of the effective component to the total weight of the solid of the wetting agent is expressed as follows:
[0095]
[0096] The preparation method of Comparative Example 1 comprises the following steps:
[0097] (1) Add 35% to 50% of the total amount of water to a container equipped with a variable speed stirrer, add a pH adjuster and a silane coupling agent in sequence, and stir until the solution is clear;
[0098] (2) Dilute the film-forming agent with 5 to 8 times its mass of water and add it into the container;
[0099] (3) Dilute the lubricant with 5 to 10 times its mass of water and add it to the container;
[0100] (4) Dilute the surfactant with 5 to 10 times its mass of water and add it to the container;
[0101] (5) Dilute the wetting agent with 5 to 10 times its mass of water and add it to the container;
[0102] (6) Finally, add the remaining amount of water to the container and stir evenly to obtain the finished product.
[0103] Comparative Example 2
[0104] The solid content of the wetting agent is 7.0%, and the percentage of the mass of each component of the effective component to the total solid weight of the wetting agent is expressed as follows:
[0105]
[0106] The preparation method of Comparative Example 2 comprises the following steps:
[0107] (1) Add 35% to 50% of the total mass of the wetting agent in water in a container equipped with a variable speed stirrer, then slowly add a pH adjuster and a silane coupling agent in sequence, and stir until the solution is clear;
[0108] (2) diluting the film-forming agent with a small amount of water and adding the diluted film-forming agent into the container, wherein the mass of the water is 3 to 5 times the mass of the film-forming agent;
[0109] (3) diluting the lubricant with water and adding it into the container, wherein the mass of the water is 5 to 10 times the mass of the lubricant;
[0110] (4) diluting the wetting agent with water and adding it into the container, wherein the mass of the water is 5 to 8 times the mass of the lubricant;
[0111] (5) diluting the surfactant with water and adding it into the container, wherein the mass of the water is 5 to 8 times the mass of the surfactant;
[0112] (6) diluting the leveling agent with water and adding it into the container, wherein the mass of the water is 5 to 6 times the mass of the leveling agent;
[0113] (7) Finally, add the remaining amount of water to the container and stir evenly to obtain the product.
[0114] Table 2 records the performance test results of the glass fiber sizing agents of Examples 1-10, Examples A1, A2 and Comparative Examples 1-2 of the present application.
[0115] Table 2 Performance test results of the embodiments and comparative examples
[0116]
[0117]
[0118] Table 2 (Continued) Performance test results of embodiments and comparative examples
[0119]
[0120] Note: (1) All data are based on 1200tex yarn test; (2) The tensile strength of the dipped yarn is based on the ASTM D2343 test standard; (3) The tensile strength of the unidirectional laminate is based on the ISO 527-5 test standard.
[0121] It can be seen from the above embodiments that by selecting the types of the components of the sizing agent and designing the content, we can obtain a sizing agent formula that meets the requirements. Compared with comparative examples 1 to 2, the glass fibers prepared by embodiments 1 to 10 of the present application and embodiments A1-A2 have good performance, good initial yarn bundling, high yarn breaking strength, high dipped yarn tensile strength, and high unidirectional laminate tensile strength. Among them, the glass fibers prepared by embodiments 3 and 5 have less hairiness, good initial yarn bundling, high yarn breaking strength, high dipped yarn tensile strength, high unidirectional laminate tensile strength, good interface bonding, and their mechanical properties are significantly better than those of products on the market.
[0122] The present application aims to provide a glass fiber impregnating agent. The glass fiber yarn produced by using the impregnating agent has the characteristics of high strength, high interface bonding and high temperature stability, excellent chemical compatibility, higher interface bonding strength and excellent permeability; the yarn is smooth to use, the product has less hairiness, and has good processability and designability. It is suitable for winding, pultrusion and prepreg processes, and is suitable for the preparation of high-pressure storage containers, launch tubes and engine casings.
[0123] Finally, it should be noted that in this article, the terms "include", "comprises" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device that includes a series of elements includes not only those elements, but also includes other elements that are not explicitly listed, or also includes elements inherent to such process, method, article or device. In the absence of more restrictions, an element defined by the sentence "comprises a ..." does not exclude the presence of other identical elements in the process, method, article or device that includes the element.
[0124] The above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them. Although the present application is described in detail with reference to the above embodiments, a person skilled in the art should understand that the technical solutions described in the above embodiments can still be modified, or some of the technical features can be replaced by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the spirit and scope of the technical solutions of the embodiments of the present application.
Claims
1. A glass fiber sizing agent, characterized in that: The invention comprises effective components and water, wherein the solid content of the wetting agent is 6.0% to 8.0%, and the effective components include silane coupling agent, film former, lubricant, wetting agent, surfactant, dry strength agent, leveling agent and pH adjuster. The percentage of the solid mass of each effective component of the wetting agent to the total solid weight of the wetting agent is expressed as follows: Silane coupling agent 10%~28%; Film former 40%~75%; Lubricant 4%~14%; Wetting agent 2%~6%; Surfactant 2%~7%; Dry strength agent 2%~10%; Leveling agent 1%~6%; pH adjuster 1%~7%; Wherein, the silane coupling agent is a mixture of an aminosilane coupling agent and an epoxysilane coupling agent; The mass ratio C1 of the aminosilane coupling agent to the epoxysilane coupling agent is 2.0:1 to 3.0:1; The film-forming agent is a mixture of bisphenol F epoxy emulsion, polyurethane emulsion and polyimide emulsion; The solid mass ratio C2 of the bisphenol F epoxy emulsion, the polyurethane emulsion and the polyimide emulsion is 3:1:0.5-4:1:1; The molecular weight of the polyurethane emulsion is 5000-10000; The molecular weight of the polyimide emulsion is 1500-2500.
2. The glass fiber sizing agent according to claim 1, characterized in that: The invention comprises effective components and water, wherein the solid content of the wetting agent is 6.0% to 8.0%, and the effective components include silane coupling agent, film former, lubricant, wetting agent, surfactant, dry strength agent, leveling agent and pH adjuster. The percentage of the solid mass of each effective component of the wetting agent to the total solid weight of the wetting agent is expressed as follows: Silane coupling agent 14%~24%; Film former 46%~68%; Lubricant 6%~12%; Wetting agent 3%~6%; Surfactant 3%~6%; Dry strength agent 4%~10%; Leveling agent 2%~6%; pH adjuster 2%~5%; Wherein, the silane coupling agent is a mixture of an aminosilane coupling agent and an epoxysilane coupling agent; The film-forming agent is a mixture of bisphenol F epoxy emulsion, polyurethane emulsion and polyimide emulsion; The sum of the solid mass percentages of the effective components of the wetting agent is 100%.
3. The glass fiber sizing agent according to claim 1, characterized in that: The aminosilane coupling agent is a bisaminosilane coupling agent, and the bisaminosilane coupling agent is selected from one or more of N-2-(aminoethyl)-3-aminopropyltrimethoxysilane, N-(β-aminoethyl)-γ-aminopropylmethyldimethoxysilane, and N-2-aminoethyl-3-aminopropyltriethoxysilane.
4. The glass fiber sizing agent according to claim 1, characterized in that: The epoxy silane coupling agent is a fat epoxy silane coupling agent, and the fat epoxy silane coupling agent is selected from one or two of 3-glycidyloxypropyltrimethoxysilane and γ-glycidoxypropyltrimethoxysilane.
5. The glass fiber sizing agent according to claim 1, characterized in that: The bisphenol F type epoxy emulsion is selected from non-ionic bisphenol F epoxy emulsion, the polyurethane emulsion is selected from cross-linked modified polyurethane emulsion, and the polyimide emulsion is selected from thermosetting polyimide emulsion.
6. The glass fiber sizing agent according to claim 5, characterized in that: The nonionic bisphenol F epoxy emulsion has a molecular weight of 300-500, a viscosity of 2000-5000 mPa⋅s, and an epoxy equivalent of 170-200 g / mol; The particle size of the cross-linked modified polyurethane emulsion is 0.1 μm-2 μm; The glass transition temperature of the thermosetting polyimide emulsion is 300 o C or above.
7. The glass fiber sizing agent according to claim 1, characterized in that: The lubricant is a silicone modified lubricant; The wetting agent is a polyether modified silicon wetting agent; The surfactant is selected from one or two of alkoxylated amine surfactants and alkoxy imidazoline surfactants; The dry strength agent is selected from one or both of polyacrylamide and polyvinyl alcohol; The leveling agent is an organic siloxane compound; The pH adjuster is citric acid and / or glacial acetic acid.
8. A method for preparing the glass fiber sizing according to any one of claims 1 to 7, characterized in that: The following steps are involved: In water accounting for 35% to 50% of the total mass of the impregnant, a pH regulator and a silane coupling agent are sequentially added, and stirred evenly to obtain a solution containing a silane coupling agent; The surfactant was added with 50 o C dilute with hot water and stir evenly to obtain a surfactant solution; The film former, lubricant, wetting agent, leveling agent, dry strength agent and solution containing silane coupling agent diluted with water are stirred evenly, then the surfactant solution is added and stirred evenly, and the remaining amount of water is supplemented and stirred evenly to obtain the glass fiber sizing agent.
9. A glass fiber produced by coating with the glass fiber sizing according to any one of claims 1 to 7.
10. Use of the glass fiber sizing agent according to any one of claims 1 to 7 in the field of high-strength glass fiber composite materials.
Citation Information
Patent Citations
Glass fiber impregnating compound as well as preparation method and application thereof
CN112777950A
Wear-resistant fiber polyurethane composite film preparation process and composite film profile
CN113858660A